Electrochemical study of the corrosion behaviour of Co-Cr-Mo orthopedic implants - Özçelik, F; Gülen, J; Akdogan, A; Piskin, S (CARL HANSER VERLAG, 1999)
A rapid growth is taking place in the use of implant material for the organs malfunctioning or injured. For this reason, search is done for material with physical and chemical resistance suitable for replacement of organs. In this study, the corrosion potential of Co-Cr-Mo alloy according to ASTM F75 at metallic implant quality was measured in open atmosphere Flank solution at 6 mV/min scanning velocity. The pH value of the blood changes as a result of infections in the human body and so, experiments were done at pH values of 4,7 and 9. Fitting potentials showed although not much but a little increase towards basic medium. Although in Co-Cr-Mo alloy grain boundary corrosion is caused it has a higher corrosion resistance than 316L austenitic stainless steel.
Keywords: Metallurgy & Metallurgical Engineering